Opportunities for improved promotion of ecosystem services in agriculture under the Water-Energy-Food Nexus - Bell, A.R.; Matthews, Nathaniel; Zhang, Wei (Springer, 2016)
In this study, we focus on water quality as a vehicle to illustrate the role that the water, energy, and food (WEF) Nexus perspective may have in promoting ecosystem services in agriculture. The mediation of water quality by terrestrial systems is a key ecosystem service for a range of actors (municipalities, fishers, industries, and energy providers) and is reshaped radically by agricultural activity. To address these impacts, many programs exist to promote improved land-use practices in agriculture; however, where these practices incur a cost or other burden to the farmer, adoption can be low unless some form of incentive is provided (as in a payment for ecosystem services (PES) program). Provision of such incentives can be a challenge to sustain in the long term, if there is not a clear beneficiary or other actor willing to provide them. Successfully closing the loop between impacts and incentives often requires identifying a measurable and valuable service with a clear central beneficiary that is impacted by the summative effects of the diffuse agricultural practices across the landscape. Drawing on cases from our own research, we demonstrate how the WEF Nexus perspective—by integrating non-point-source agricultural problems under well-defined energy issues—can highlight central beneficiaries of improved agricultural practice, where none may have existed otherwise.